2016
DOI: 10.1002/cptc.201600025
|View full text |Cite
|
Sign up to set email alerts
|

The Flavin–Tryptophan Dyad F10T as a Cryptochrome Model Compound: Synthesis and Photochemistry

Abstract: Many animals sense the Earth's magnetic field and use it for navigation. It has been proposed that a light‐dependent quantum effect in cryptochrome photoreceptor proteins residing in the retina allow for such an iron‐free spin‐chemical compass. The primary photochemistry in cryptochromes and photolyases is assumed to be confined mainly in a flavin adenine dinucleotide (FAD) residue and three nearby tryptophan residues. Functional studies require model compounds allowing for direct structural modifications. Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This slow process is presumably because of the strong exchange interaction between the two radical-centres. Due to strong coulomb interaction between the positive and the negative charge-centre (radical-centre), in these energy-states the biradicals obtain a deformed-Z-shaped conformation with reduced separation between the radical-centres compared to the Z-shaped conformation 27 . According to the conservation of spin angular momentum, during the fast electron transfer, the radical pair is formed with the same spin multiplicity as its precursor species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This slow process is presumably because of the strong exchange interaction between the two radical-centres. Due to strong coulomb interaction between the positive and the negative charge-centre (radical-centre), in these energy-states the biradicals obtain a deformed-Z-shaped conformation with reduced separation between the radical-centres compared to the Z-shaped conformation 27 . According to the conservation of spin angular momentum, during the fast electron transfer, the radical pair is formed with the same spin multiplicity as its precursor species.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis details of F10T are given in Paul et al . 27 . All the solutions were prepared in methanol-d 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No photolyase activity has been reported for cyclobutane pyrimidine dimers or 6–4 photoproducts; however, this protein is known to contribute to sensing Earth’s magnetic field in D. melanogaster [ 20 , 21 ]. This Cry activation is intermediated by radicals [ 10 , 36 ]. Hoang et al [ 36 ] reported that a Cry protein subfamily, which does not possess the light response, also showed photoreaction.…”
Section: Discussionmentioning
confidence: 99%
“…Evoked electrons under EMFs can affect chemical signaling in cell communications. Paul et al [ 10 ]. reported that EMFs at higher frequencies play an important role in sensing directions, especially in birds.…”
Section: Introductionmentioning
confidence: 99%